Transepithelial Versus Conventional PRK: A Randomized Controlled Study - Robert Edward T. Ang (Ophthalmology and Therapy)
Abstract Introduction Transepithelial photorefractive keratectomy (t-PRK) is an updated maneuver based on the proven surgical procedure of conventional photorefractive keratectomy (PRK) for the correction of ametropia. Unlike conventional PRK, which is a two-step process involving the physical removal of the corneal epithelium prior to excimer laser treatment of the stroma, t-PRK uses the excimer laser to complete both activities in a single-step procedure. Methods This was a prospective, randomized, controlled, contralateral, masked, single-surgeon study of adult subjects with myopia with a manifest residual spherical equivalent (MRSE) of ≤ 1.5 D or hyperopia with an MRSE of ≥  + 1.5 D, conducted at a single center in the Philippines. Eligible subjects were randomized to undergo conventional PRK in one eye and t-PRK in the other. The follow-up was for 6 months. The primary endpoint evaluated the absolute refractive predictability at 3 months. Secondary endpoints during the 6-month follow-up included safety, manifest refraction, visual acuity, halos and glare, slit-lamp examinations, and patient-reported outcomes. Results A total of 35 subjects (70 eyes) were enrolled (63% female, 94% Asian, mean age 30 years). The mean (standard deviation [SD]) absolute prediction error was 0.26 D (0.23) for conventional PRK and 0.34 D (0.32) for t-PRK, meeting the threshold for demonstration of noninferiority (p = 0.2253). There were no statistically significant differences between conventional PRK and t-PRK for manifest sphere, manifest cylinder, MRSE, or uncorrected or corrected visual acuity at 6 months. All subjects were satisfied with both procedures and there was no preference for one treatment over the other. Conclusions Both conventional and t-PRK are equally safe and effective, and result in favorable outcomes for subjects with ametropia. The efficiency of the t-PRK procedure versus conventional PRK should be considered when PRK is indicated. Trial Registration ClinicalTrials.gov, NCT04698174.